PENGARUH STATUS GIZI TERHADAP FERTILITAS WANITA: LITERATURE REVIEW - Rista Dwi Hermilasari Rista; Septy Handayani; Nurul Ulya Luthfiyana (SINERGI : Jurnal Riset Ilmiah, 2026)
Infertility is a reproductive health issue influenced by various factors, including nutritional status. Nutritional status is a modifiable determinant that plays an important role in the regulation and maintenance of reproductive function. Both undernutrition and overnutrition have the potential to affect female reproductive function through metabolic, hormonal, and inflammatory mechanisms. This study aimed to provide a comprehensive overview of the influence of nutritional status on female fertility. A literature review was conducted by searching articles in the Scopus, PubMed, and ScienceDirect databases using the keywords nutritional status, obesity, overweight, malnutrition, body mass index, female fertility, infertility, and reproductive health. The findings indicate that nutritional status has a complex relationship with female fertility. Increased adiposity and obesity may adversely affect reproductive function, including ovarian reserve, oocyte quantity, reproductive outcomes, and the risk of obstetric complications. In addition, relative fat mass has the potential to be a more sensitive indicator than body mass index for evaluating the risk of female fertility disorders. Therefore, the use of more comprehensive adiposity indicators is needed to improve the understanding of the relationship between nutritional status and female fertility.